Cardiac computed tomography‐derived myocardial tissue characterization after anthracycline treatment - Koichi Egashira; Daisuke Sueta; Masafumi Kidoh; Mai Tomiguchi; Seitaro Oda; Hiroki Usuku; Kaori Hidaka; Lisa Goto‐Yamaguchi; Aiko Sueta; Takashi Komorita; Fumi Oike; Koichiro Fujisue; et al. (ESC Heart Failure)
Abstract Aims Understanding cardiac function after anthracycline administration is very important from the perspective of preventing the onset of heart failure. Although cardiac magnetic resonance and echocardiography are recognized as the ‘gold standard’ for detecting cardiotoxicity, they have many shortcomings. We aimed to investigate whether cardiac computed tomography (CCT) could replace these techniques, assessing serial changes in cardiac tissue characteristics as determined by CCT after anthracycline administration. Methods and results We prospectively investigated 15 consecutive breast cancer patients who were scheduled to receive anthracycline therapy. We performed echocardiography and CCT before and 3, 6, and 12 months after anthracycline treatment. The mean cumulative administered anthracycline dose was 269.9 ± 14.6 mg/m2 (doxorubicin‐converted dose). Of the 15 enrolled patients who received anthracycline treatment for breast cancer, none met the definition of cardiotoxicity. The CCT‐derived extracellular volume fraction tended to continue to increase after anthracycline treatment and had relatively similar dynamics to the left ventricular ejection fraction and global longitudinal strain as determined by echocardiography. Conclusions Our findings indicated that CCT could provide adequate information about the characteristics of myocardial tissue after anthracycline administration. CCT may improve the understanding of cardiotoxicity by compensating for the weaknesses of echocardiography. This technique could be useful for understanding cardiac tissue characterization as a ‘one‐stop shop’ evaluation, providing new insight into cardiooncology.